PLANT SPECIES DIVERSITY IN RELATION TO CARBON STOCKS AT JANGKOK WATERSHED, LOMBOK ISLAND - Markum, Markum; Soesilaningsih, Endang Arie; Suprayogo, Didik; Hairiah, Kurniatun (AGRIVITA, Journal of Agricultural Science, 2013)
ABSTRACTThe area around Jangkok watershed has changed, dividing it into some land use systems. This research aimed to study the effect of plant species diversity onC-stocks, and to analyse the characteristics of land use systems based on their similarity. The observations were carried out on 18 plots representing six land use systems in Jangkok watershed (Lombok Island) i.e. primary forest (PF), disturbed forest (DF), Mahogany- woodlot (MW), candlenut- agroforestry (CA), multistrata- agroforestry (MA), and simple- agroforestry (SA).The species diversity level was measured using Shannon-Weiner diversity index, whileC-stocks according to the method of RaCSA (Rapid Carbon Stock Appraisal). Results showed that forest conversion to agricultural land usesreduced the number and density of the species, average wooddensity andtree basal area. The PF represented the highest biodiversity index (3.46), while the other land uses were categorised in medium and low. Largest C-stock wasfound inPF and in(30 years old) of MWaveraged of 500 Mg ha-1, while the lowest was in SAof 68 Mg ha-1, while in other land uses was 219 Mg ha-1.The quantity of C-stock was not related tospecies diversity and its density, but closely related (pof tree (R2=0.84), basal area of all sizes tree (R2=0.86), and with the basal area of big trees (diameter > 30 cm) (R2=0.71). Based on the number and species density, agroforestry system (MA and CA) resembled the characteristics of natural forest (DF and PF)./spanEN-GBspan style=